147k views
4 votes
This................................................................................................

This................................................................................................-example-1
User Spekdrum
by
6.0k points

2 Answers

4 votes

Answer:

5

Explanation:

minus * minus = plus

3-(-2) = 3 + 2 = 5

User Drakosha
by
6.8k points
5 votes

Answer:

5

Explanation:

3-(-2)

the two negative signs cancel out and it turns into

3 + 2

3 + 2 = 5

User Cantelope
by
5.9k points